Entrepreneurial intention, job satisfaction and organisation commitment: Construct of a research model through literature review - Kh. Devananda Singh; B. D. Onahring (Journal of Global Entrepreneurship Research, 2019)
Intention is a human behavior. Measurement of intention in terms of entrepreneurial mindset is becoming a researchable topic. During the past years, the factors namely lack of fund, lack of raw materials, unskilled employees etc. were mostly considered to be the deterrents of initiation and development of entrepreneurial activities. But, with the various development provisions are made by the concern authorities, it leads to the emergence of entrepreneurial intention as an important factor. The present paper is a humble effort to develop a research model of the relationship between entrepreneurial intention, job satisfaction and organisation commitment.
Keywords: 650; Entrepreneurial intention; Job satisfaction; Organisation commitment; Research model